Here have another one - Unknown (Tufts Archival Research Center, 2018)
Political cartoon of President Richard Nixon offering a second cigar with the word "Cambodia" written on it to a man. The man's first cigar--entitled "Vietnam"--has just exploded. This is a scan of one of four duplicate posters in the folder.